Determinants of prelabor rupture of membrane among pregnant women attending governmental hospitals in Jimma zone, Oromia region, Ethiopia: A multi-center case-control study. - Ebrahim Msaye Assefa; Getachew Chane; Addis Teme; Tilahun Alemayehu Nigatu (PLoS ONE, 2023)
Background Prelabor rupture of membrane defined as the rupture of fetal membranes before the beginning of uterine contractions, is a common complication of pregnancy and the leading cause of preterm birth. In Ethiopia, the prevalence of prelabor rupture of membrane varied significantly between settings due to variations in risk factors. Besides, there was no study conducted using primary data, particularly in the Jimma zone, Ethiopia. Therefore, this study aimed to identify determinants of prelabor rupture of membrane among pregnant women attending governmental hospitals in the Jimma zone, Oromia region, Ethiopia. Methods An institutional-based unmatched case-control study design was conducted from October 15 to December 15, 2021, at four governmental hospitals. A consecutive sampling technique was used to select 316 participants (79 cases and 237 controls). Women with prelabor rupture of the membrane were confirmed by history, sterile vaginal examination, and ultrasound as cases, and their counterparts as controls. An interviewer-administered questionnaire was used to collect data on maternal (obstetric, medical, behavioral) and fetal-related characteristics. The data were entered into Epi Data version 4.6 and analyzed using SPSS version 25. Descriptive statistics, bi-variable, and multivariable logistic regression were computed. The odds ratio with a 95% confidence level was used, and the significance level was declared at a p-value < 0.05. Results A total of 316 participants (79 cases and 237 controls) were included in this study. Pregnancy-induced hypertension (AOR = 3.06, 95% CI: 1.41-6.64), history of abortion (AOR = 3.67, 95% CI: 1.56-8.65), urinary tract infections (AOR = 2.61, 95% CI: 1.13-6.06), abnormal vaginal discharge (AOR = 2.65, 95% CI: 1.21-5.79), maternal khat chewing (AOR = 3.40, 95% CI: 1.70-6.80), mid-upper arm circumference less than 23 cm (AOR = 2.80, 95% CI: 1.51-5.19), and fetal presentation (breech) (AOR = 2.63, 95% CI: 1.10-6.28) were determinants of prelabor rupture of membrane among pregnant women. Conclusion This study revealed that the aforementioned factors were found to be determinants of prelabor rupture of membrane among pregnant women. Therefore, hospitals should give focus to the early screening, diagnosis, and treatment of pregnancy-induced hypertension, urinary tract infection, and abnormal vaginal discharge to reduce the burden of prelabor rupture of membranes.